Installation and cosmic ray test of the high voltage system of the BESⅢ drift chamber - 徐美杭 陈昌 陈元柏 吴智 秦中华 伍灵慧 刘建北 王岚 金艳 刘荣光 朱启明 张健 黄杰 (Chinese physics C, 2008)
After examination of the designed high voltage power supply system of the BESⅢ drift chamber in the beam test of the full length prototype of drift chamber, a full system covering all the channels of high voltage was installed. The system＇s training and the high voltage value adjustment were carried out in the cosmic ray test of the BESⅢ drift chamber. The cosmic ray test for the full system and its final installation on the BESⅢ drift chamber were reported. The full system of high voltage power supply works stably and reliably.